G96 Stevens-Johnson syndrome and toxic epidermal necrolysis associated with lamotrigine treatment in children: A review of 486 individual case safety reports. (27th April 2016) - Egunsola, O; Star, K; Juhlin, K; Choonara, I; Sammons, H
Abstract : Aim: SJS and TEN are life-threatening conditions, usually secondary to drug therapy. This study explored the characteristics of children with Stevens – Johnson syndrome (SJS) and Toxic epidermal necrolysis (TEN) following lamotrigine (LTG) treatment to identify potential risk factors. Methods: A retrospective review of individual case safety reports (ICSRs) of SJS and TEN in LTG treated children. ICSRs were acquired from the WHO international database of suspected ADRs, which stores ADRs from national pharmacovigilance centres worldwide. Case reports of paediatric patients, ≤17 years old, were retrieved and compared with cases of LTG associated non-dermatological ADRs, cases of SJS/TEN not associated with LTG and reports of SJS/TEN associated with carbamazepine (CBZ) and phenobarbital (PBT). Results: There were 486 reports of SJS/TEN in LTG treated children. The proportion of SJS/TEN reports in LTG and VPA co-medicated patients was significantly higher than the proportion reporting non-dermatological ADRs when taking both drugs (logOR 1.60; 99% CI: 1.33, 1.84). A significantly higher proportion of cases of SJS/TEN, compared with all ADRs, were also reported with LTG and VPA co-medication (logOR 1.23; 99% CI: 0.96–1.47); while no significant difference was seen in the proportion of SJS/TEN reports with CBZ or PBT and VPA co-medication. Ninety six percent of the cases of SJS/TEN occurred within 6 weeks of initiation of LTG therapy. The median time to onset was 15 days [IQR: 10.8–22 days]. Conclusions: LTG and VPA co-medication significantly increases the risk of SJS/TEN, which is likely to occur within 6 weeks of treatment in most children.